ŠTERNBERK HOSPITAL - Hospital, Šternberk (Biomedical papers, 2005)
Šternberk Hospital is a regional hospital disposing of 250 beds currently. Its Olomouc operational area covers over 100,000 inhabitants. However, some departments ofthis hospital provide care for other catchment areas in the Czech Republic and in some cases specialised medical examinations for the whole CR. Šternberk Hospital for instance houses the Department of Laboratory Medicine (DLM) (www.nemstbk.cz/olm) which employs 52 persons (12 physicians, 10 chemistry graduates, 20 laboratory technicians, 5 collection nurses, 1 dietary nurse, 2 administrative workers, 1 LIS administrator and 1 auxiliary worker).
Keywords: ŠTERNBERK HOSPITAL